MICROORGANISMS AS RISK FACTORS AND PROTECTION OF WOMEN'S REPRODUCTIVE HEALTH: AN ANALYSIS OF THE CURRENT LITERATURE - Hafsan, Hafsan; Febriyanti, Ayu; Nur Hanisa, Andi; Suryaning Amanda, Sabilla (JURNAL SIPAKALEBBI, 2024)
Women’s reproductive health is significantly influenced by the intricate relationship between microorganisms and the body, where both pathogenic and beneficial microorganisms play critical roles. Pathogenic microorganisms, such as Chlamydiatrachomatis, Neisseria gonorrhoeae, and Gardnerella vaginalis, are often associated with reproductive tract infections, leading to conditions such as bacterial vaginosis (BV) and sexually transmitted infections (STIs). These conditions increase risks for serious complications, including infertility and pregnancy-related issues. On the other hand, beneficial microorganisms, especially Lactobacillus species, contribute to vaginal health by maintaining an acidic pH and producing antimicrobial substances that protect against pathogenic invasions. This review discusses the role of microorganisms as both risk factors and protective agents in women’s reproductive health. Addressing the impact of hormonal variations, hygiene practices, contraception, and lifestyle factors on vaginal microbiota composition. Furthermore, the potential of probiotic therapy to restore microbiota balance and prevent infections is explored. Understanding these dynamics may inform more targeted and effective therapeutic strategies to promote reproductive health. Additional research is needed to optimize probiotic therapies, develop personalized interventions, and leverage advancements in multi-omics technologies to further elucidate microbiota-health interactions.